Analysis of University Student Satisfaction Levels with the Learning Process on Five Dimensions of Service Quality (SERVQUAL) - Rahmawati Rahmawati; Johar Permana; Diding Nurdin; Cepi Triatna; Fadhli Fadhli (AL-ISHLAH: Jurnal Pendidikan, 2023)
Each academic course must conduct a self-evaluation, one method of which is a survey of students' attitudes towards the teaching and learning they experienced. Service quality affects how satisfied students are with the institution. There are five service quality dimensions (SERVQUAL): Reliability, Responsiveness, Assurance, Empathy, and Tangible. The purpose of the study was to analyze students' level of satisfaction with the learning process on the 5 SERVQUAL Dimensions and evaluate which dimension had the highest level of satisfaction. The object of research is the active students of Almuslim University in the Odd Semester of the Academic Year 2021/2022 totalling 1,023 people. Quantitative research approach with the type of survey research. Data was collected using a Google form questionnaire which was distributed online. Analysis of the data by calculating the Percentage of Respondents' Achievement Level (RAL) followed by calculating the Community Satisfaction Index (CSI). The results showed that the highest RAL was in the Assurance Dimension, the average score was 3.23, and the RAL was 80.65% (excellent category), while the lowest RAL was in the Tangible Dimension, the average core was 3.06, and the RAL was 76.44% (excellent category). Analytical findings on a per-item basis There are five areas that need tweaking: The incorporation of e-learning technology and instructor feedback into the classroom setting. Hotspot facilities, as well as learning facilities in the lecture room, are readily available to accommodate the lecturers' high availability for academic consultations and/or Final Project discussions. The Assurance Dimension received the greatest CSI score (3.23), and the highest CSI conversion score (80.65), while the Tangible aspect received the lowest CSI score (2.94), and the lowest CSI conversion value (73.38). Overall, we received a CSI conversion score of 79.45, for a grand total of 3.18 (good).